The effect of Oroxylum indicum leaves methanolic extract towards VCAM-1 expression on hela cells - Keflee, Rashidi Dzul (Universiti Sains Malaysia, 2016)
Cervical cancer is the fourth most common cancer in women, and the seventh overall, with an estimated 528,000 new cases in 2012. Cervical cancer ranks as the third female cancer in among women aged 15 to 44 years in Malaysia. Oroxylum Indicum (O. indicum) is a medium-sized deciduous tree with high economical, ecological and medicinal importance. This plant which also known as Indian trumpet tree can easily be found in many tropical countries. The leaves are traditionally used as stomachic, carminative and flatulent. VCAM-1 interact with the ligands expressed on the surface of the vascular endothelial cells and responsible for selective recruitment of different leucocyte into the blood and extravasation to the tissue. Cancer utilize these mechanism to form secondary tumor site and increase metastases of cancer. The aim of this study is to examine the effect of O.indicum leaves methanolic extract (MEOIL) towards VCAM-1 expression on HeLa cells. In vitro anti-proliferative activity of MEOIL extract towards HeLa cells was determined by Methylene Blue Assay (MBA) for IC50 determination. HeLa cells were stimulated with TNF-a for one hour, prior to 24 hours treatment with MEOIL. Determination of VCAM-1 expression was conducted via flow cytometry analysis (FCS) by surface staining. MEOIL extract shows the anti-proliferative effects on HeLa cells with IC50 of 3.10 pg/ml, which is lower than cisplatin (positive control) with IC50 of 9.86 pg/ml. The surface expression of VCAM-1 is decreased in MEOIL-treated HeLa cells compared to untreated cells. TNF-a treatment was able to increase the expression of VCAM-1 and further treatment of HeLa cells with MEOIL showed a decreased expression of VCAM-1. In conclusion, the MEOIL could down-regulate the VCAM-1 expression in cervical cancer cell which could reduce the metastases of cancer and decrease the progression of cervical cancer.